Peran Guru Penggerak Dalam Implementasi Kurikulum Merdeka Pada Era Digital - Firmansyah, Alfitra; Sutrisno, Sutrisno; Huda, Luthfi Nurul; Herlambang, Muhammad (PAKAR Pendidikan, 2024)
Driving teachers are educators who encourage the comprehensive growth and development of students, actively and proactively guiding other teachers to implement student-centered learning. They also act as catalysts for change in the surrounding community, especially in increasing the Pancasila Student Profile among students. This research uses a qualitative approach, where this qualitative approach will examine the role of driving teachers in implementing the independent curriculum in the digital era. The method used in this research is the critical analysis method. This method aims to process the evaluation and assessment of a topic or idea by considering existing arguments and evidence. The research results show that driving teachers through an active and competent role in implementing the independent curriculum, especially in the current digital era, driving teachers can create a dynamic, interesting and relevant learning environment for students. They help students develop the skills necessary to succeed in an ever-evolving digital world. They need to have a deep understanding of the independent learning curriculum, analyze school needs and context, develop appropriate learning materials and resources, collaborate with fellow teachers, carry out monitoring and evaluation, and continue to improve their professionalism. By taking these steps, driving teachers can become a driving force in implementing the independent learning curriculum in the digital era, which is more effective and successful in schools.